The Effect of Training and Teaching Experience on Teacher Performance State Basic Schools - Kencana, Voulinda; Arafat , Yasir; Putra, Alhadi Yan (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study uses a quantitative method with a correlational approach, namely using numerical analysis. This research will be carried out in all elementary schools in Muara Dua Kisam District, South Oku Regency. Collecting data in this study using a questionnaire. The conclusion that can be drawn from the results of research and discussion is that there is a positive and significant influence between training on the performance of elementary school teachers in Muara Dua Kisam District with an rX1Y value of 0.434> r table, namely 0.278, so there is a positive influence between training on school teacher performance. based in Muara Dua Kisam District. The R square value is 0.188, which means that 18.8% of teacher performance is affected by training. with a significant t of 0.002 <0.05. The conclusion that can be drawn from the results of research and discussion is that there is a positive and significant influence